A Rare Case of Metastatic Gall Bladder Polyp Secondary to Renal Cell Carcinoma - Dhawan, Ankita; Dembla, Sagar; Goswami, Gaurav (Asian Journal of Medical Radiological Research, 2021)
Metastatic origin of Gall bladder polyp is usually associated with either gastric carcinoma or melanoma. Whereas, its association with Renal cell carcinoma is a rare occurrence. Its prevalence in autopsies is reported to be around 0.6%. Here, we present a case of 73-year-old gentleman, diagnosed with renal cell carcinoma 2 years back and underwent radical nephrectomy. During his routine follow-up, ultrasound revealed a gall bladder polyp which was about 28 mm in size. He underwent open cholecystectomy and histopathological analysis revealed it as a metastatic deposit. Hence, suggestive of metachronous gall bladder polyp in renal cell carcinoma.